The profile of ingressing biology students in the high school of Barreirinhas (Research, Society and Development, 2020)
The present work had for objective to know the profile of the students students of the subject of Biology recently entered in the High School of Barreirinhas (MA). The study was carried out in the municipality of Barreirinhas (MA), with three public schools in the city as a research field, and 180 students (60 for each institution) as the target audience. All students were recently enrolled in high school (first year students of the sport). The survey used questionnaires as an instrument for data collection, with open and closed questions. The results present information that describes the profile of the students, such as the students' genders, areas of housing, average age, types of schools that attended elementary school, the opportunity to have or not studied science in elementary school and how these students went through the Science curriculum component. Most students have very similar characteristics, such as having the age group between 15 and 19 years old, as well as having the Urban Area as their main housing area, in addition to the technically equal number of men and women in the same space. school. Absolutely, the vast majority of students attended elementary school only in public intuitions, as well as had the opportunity to have always attended the discipline of Science, in addition to not having failed the discipline, despite a considerable portion of students who declared having faced very difficult to get approval in this matter.